NEW SCINCID LIZARD OF THE GENUS SPENOMORPHUS (REPTI~ SCINCIDAE), FROM JAVA - DJOKO ISKANDAR (Treubia, 1994)
Sphenomorphus puncticentralis m.sp. is described based on a single specimen from Baturaden, Central Java, and is considered to belong to the variegatus species. The scincid lizard genus Sphenomorphus is represented by five species, i.e. S. temmincki, S. recopinatum, S. vanheurni, S. florensis and S. sanctum. The occurence of a new species in Java seems to be unlikely. However, during a field trip to Central Java in 1979, a skink specimen was collected, captured on a small tree in an open secondary forest during morning hours. The skink turned out to be an undescibed species of the genus Sphenomorphus. Effort to get additional specimens, a second trip to the same locality in 1986 failed since the original habitat has changed into' an Agathis forest. Despite of scarcity of specimens description is given hereunder based on a single specimen. This new skink is described as Sphenomorphus puncticentris based on the presence of the black spot on the dorsal scales on the paravertebral line region.